A Narrative Review of Pediatric Nontraumatic Spinal Cord Dysfunction - New, Peter Wayne (Top Spinal Cord Inj Rehabil, 2019)
This article provides a narrative review of seven key issues relevant to pediatric onset of spinal cord damage not due to trauma, or spinal cord dysfunction (SCDys). The first topic discussed is terminology issues. There is no internationally accepted term for spinal cord damage not due to trauma. The implications of this terminology issue and an approach to addressing this are discussed. Second, a brief history of SCDys is presented, focusing on conditions relevant to pediatrics. Third, the classification of SCDys is outlined, based on the International Spinal Cord Injury Data Sets for Non-Traumatic Spinal Cord Injury. Following this, a summary is given of the epidemiology of pediatric SCDys, primarily focused on the incidence, prevalence, and etiology, with a comparison to traumatic spinal cord injury. Next, important clinical rehabilitation principles unique to children with SCDys are highlighted. Then important prevention opportunities for SCDys in children are discussed. Finally, trends, challenges, and opportunities regarding research in SCDys are mentioned.